ICT litpro portal / Teng Yi Dung - Teng, Yi Dung (2004)
ICT LitPro Portal is a web based multimedia learning system for lower secondary level. ICT LitPro is designed to-create an information rich environment of knowledge that is accessible and available, The users of the portal are categorized into 3 main groups mainly the Administrators, Registered Members and the Non-Registered Members. The JCT LitPro Portal includes 6 modules which are the Authentication, User Management, Lesson Management, Test Management, Search Function and the Discussion Board. ICT LitPro Portal will be developed using Microsoft Active Server Pages technology. The other development tools include Windows XP Professional, Microsoft Internet Information Server 5.0. Microsoft SQL Server 2000 and also Macromedia Dreamweaver MX. Administrators will be maintaining the portal by tracking all activities in the portal. They will be supervising all the authentication process for login and logouts, the lessons management, test management and not to mention the discussion board. Registered Members will be able to engage in User Management, where they will be able to edit their own user profile, get a temporary user id and password in case they forgot it. They will also be able to participate in the tests given out after following the lessons for a period of time. The lessons given will include Advanced Word Processing, Advanced Graphics and Presentation, Spreadsheet, the Internet and the World Wide Web. Non-Registered Members will only be able to view the lesson plans provided for an overview of what the whole lessons arc all about. They will only be able to join in as a Registered Member after registering as a member and paying an amount of fee through credit card transaction. All in all, it is hoped that this information gateway will be able to achieve its goals in meeting the rapid changing needs of today's education environment. Last but not least, it is important to stress that this project is not intended to take place of teachers. It is merely a teaching and self-learning aid that acts as a supplementary to the core curriculum supplied by schools.